1987
DOI: 10.1007/bf02366189
|View full text |Cite
|
Sign up to set email alerts
|

A critique of traditional approaches to seaweed distribution in light of the development of vicariance biogeography

Abstract: An overview of the primary approaches to seaweed biogeography is provided in light of the development of vicariance biogeography. Each approach is discussed with particular regard to the extent to which the methods and objectives are compatible with vicafiance. Ecological biogeography is considered an offshoot of ecology and physiology and is more appropriate in determining current distributions of organisms and aspects of physiological ecology rather than the spedation history of monophyletic groups. The R/P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The acceptance of the plate tectonic theory in the late 1960s inspired largely vicariant explanations of such broad distributions (e.g. Garbary 1987, Chin et al 1991, with many historical biogeographers tending towards the view that species distributions are driven more by long-term geological processes than by dispersal events (Nelson & Platnick 1981, Humphries & Parenti 1999, Ebach & Tangney 2007. The increasing use of molecular data in biogeographical research has, however, demonstrated that general (multitaxon) biogeographical patterns can be generated via long-distance oceanic dispersal events, if the mechanism allowing for dispersal operates steadily over long periods (see review by Sanmartín et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The acceptance of the plate tectonic theory in the late 1960s inspired largely vicariant explanations of such broad distributions (e.g. Garbary 1987, Chin et al 1991, with many historical biogeographers tending towards the view that species distributions are driven more by long-term geological processes than by dispersal events (Nelson & Platnick 1981, Humphries & Parenti 1999, Ebach & Tangney 2007. The increasing use of molecular data in biogeographical research has, however, demonstrated that general (multitaxon) biogeographical patterns can be generated via long-distance oceanic dispersal events, if the mechanism allowing for dispersal operates steadily over long periods (see review by Sanmartín et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Table 3. Feldmann (1937) and Cheney (1977) The Feldmann (1937) and Cheney (1977) indices have been used extensively as a general measure of the arctic to tropical nature of floras (see discussion of these metrics in Garbary 1987). Using the revised species totals from this study one can calculate the indices for the Keret Archipelago and other subarctic areas (Table 3).…”
Section: Flowering Plantsmentioning
confidence: 99%
“…This fact was exploited by Croizat (1958) in his panbiogeography, a method which synthesises data from geology, zoogeography and phytogeography. Garbary (1987) has recently suggested that panbiogeographic track analysis could make an important contribution to seaweed studies.…”
Section: Other Taxa With Similar Distribution Patternsmentioning
confidence: 99%